Synthesis of Alkoxycarbonyldifluoromethyl-Substituted Semisquarates and Their Transformations - Kurohara, Takashi; Jiyue, Jiang; Shibuya, Masatoshi; Yamamoto, Yoshihiko (Synthesis, 2018)
A novel EtO2CCF2-substituted semisquarate is synthesized from diisopropyl squarate by selective 1,2-addition of the Reformatsky reagent derived from BrCF2CO2Et and subsequent rhenium-catalyzed allylic alcohol rearrangement. The compatibility of the highly reactive EtO2CCF2 group in ring transformations of the obtained semisquarate is investigated. Various EtO2CCF2-substituted, highly functionalized compounds, such as quinones, tetronates, cyclopentenones and a bicyclo-[3.2.0]heptenone, are successfully synthesized by ring transformations of the EtO2CCF2-substituted semisquarate. Also, an allylO2CCF2-substituted semisquarate is prepared and converted into the corresponding tetronate. Subsequent palladium-catalyzed deallylation followed by condensation of the resulting carboxylic acid with several amines under mild conditions affords the corresponding α,α-difluoroamides in good yields.
Keywords: squarate; ring expansion; fluorine; quinones; tetronates; cyclopentenones